Analisis Efisiensi Penggunaan Faktor Produksi Usahatani Cabai Merah di Desa Besakih, Kecamatan Rendang, Kabupaten Karangasem - WIJAYANTI, NI WAYAN ADIYANI; DEWI, RATNA KOMALA; WIDIYANTARA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Efficiency Analysis of The Use Of Red Chili Production Factors in Red Chili Farming at Besakih Village, Rendang, Karangasem The research was conducted in Besakih Village, Rendang Sub-District, Karangasem Regency which is one of red chili farming centers in Karangasem Regency. The problem is that production tends to decline over the past five years. This study aims to analyze the effect of production factors and the level of efficiency of the use of red chili production factors on the red chili production in Besakih Village. The method used to analyze the factors of production was the Cobb-Douglas production function. Data were obtained from 62 respondents by census method. Efficiency was calculated by analyzing the ratio of marginal production prices to factor prices. The results showed that production factors that affect the amount of production include land, seed, manure, NPK, leaf fertilizer, calcium fertilizer, pesticides, and labor. Simultaneously, the influence of production factor was 93,90% to the amount of red chili production, while partially, factors that affect the production of red chili were seed, manure, NPK and pesticide. The production factor that has been efficient in its use was NPK fertilizer. Factors of seed production and manure have not been efficient, so their use needs to be added. Leaf fertilizer production factors, calcium fertilizers, pesticides, and labor usage were inefficient, so the use needs to be reduced.